Dos ideas claves: ¿cómo aprender y enseñar competencias? - De Cárdenas Mazzetti, María José (2011)
The present article is about two main ideas about competences, the first one explains the relationship among knoledge, abilities and attitudes dealing with competence because it is important to considerthese three aspects. In the other hand why memorization and comprehension go by the same way of knowledge and procedures with the development of competences.The second idea is related to the object of education is the development of the person. This suposes to say that competence goes beyond the professional arena and affects the whole life of a person.